Individual factors influencing the duration of untreated psychosis. Issue 4 (25th March 2018) - Souaiby, Lama; Gauthier, Claire; Kazes, Mathilde; Mam‐Lam‐Fook, Célia; Daban, Claire; Plaze, Marion; Gaillard, Raphaël; ,; Krebs, Marie‐Odile
Abstract : Aim: Duration of untreated psychosis (DUP), or the time between onset of psychosis and treatment initiation, is a prognostic factor of schizophrenia. However, few studies evaluated the relative influence of individual‐related factors on this duration. The objective of this study was to evaluate the influence of socio‐demographic, clinical and cannabis use on DUP. Methods: This study was part of a large prospective study in help‐seeking individuals referred to our specialized early detection / intervention clinic in the Service Hospitalo‐Universitaire of Sainte‐Anne Hospital in Paris (ICAAR study). We explored 33 consecutive patients who crossed the CAARMS' threshold of psychosis. The DUP and cannabis consumption history were explored during the baseline comprehensive assessment using all available sources (direct interviews of patients, parents, practitioners). Correlations between socio‐demographic, clinical and cannabis use, and DUP were studied. A multiple linear regression model was used to determine the variables that could significantly predict DUP. Results: When considered individually, none of the socio‐demographic and disease characteristic factors was associated with DUP, with the exception of level of education. In the multivariate analysis, age at inclusion, negative symptoms and history of cannabis use significantly influenced DUP. Conclusion: The determinants of DUP are multi‐factorial and include individual centred factors, such as age, cannabis and negative symptoms. The identification of factors resulting in delayed access to care may promote the development of effective strategies to reduce DUP in early psychosis and target effective early intervention.